1984
DOI: 10.1002/eji.1830140421
|View full text |Cite
|
Sign up to set email alerts
|

Surface markers of cytotoxic T lymphocyte clones

Abstract: Several class II major histocompatibility complex antigen-specific murine cytolytic T cell clones express Lyt-2 but not MT4 surface antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This situation may apply to many of the Lyt-2' L3T4-class II-restricted T-cell clones documented in the literature (9) in which Lyt-2 appears to have no function. In other cases, inhibition studies with anti-Lyt-2 have not been performed (26). However, there does appear to be evidence of functional L3T4 in an unusual class I-restricted hybridoma (20).…”
Section: Discussionmentioning
confidence: 99%
“…This situation may apply to many of the Lyt-2' L3T4-class II-restricted T-cell clones documented in the literature (9) in which Lyt-2 appears to have no function. In other cases, inhibition studies with anti-Lyt-2 have not been performed (26). However, there does appear to be evidence of functional L3T4 in an unusual class I-restricted hybridoma (20).…”
Section: Discussionmentioning
confidence: 99%
“…Positive selection ensures that T cells respond to foreign antigens in conjunction with self-MHC molecules [1][2][3]. This is achieved by allowing T cells recognizing self peptides presented by self-MHC molecules to mature, resulting in differentiation of CD4 + CD8 + TCR low double-positive (DP) thymocytes into CD4 + CD8 -TCR high or CD4 -CD8 + TCR high singlepositive (SP) T cells [4][5][6]. Negative selection screens for thymocytes recognizing self peptides with high affinity and leads to elimination or inactivation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical examinations revealed that the great majority of intraepidermal infiltrates were CD8+, and CD4+ cells were rarely seen in the cutaneous lesions. Although it seems a well established idea that CD8+ cells selectively respond to MHC class I antigens (review by Swain, 1983), there have been several reports of MHC class IIreactive CD8+ T cell clones (Haas & von Boehmer, 1984;Golding & Singer, 1985;Shinohara & Kojima, 1984). The functions of MHC class II-reactive CD8+ cells in vivo are still unknown.…”
Section: Discussionmentioning
confidence: 99%